1969
DOI: 10.1002/cber.19691021106
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung verschieden substituierter 1‐Benzolazo‐alkene und Additionsprodukte

Abstract: Die I-Benzolazo-LyLlohexene-~l) 4a 4e (analog I-Benzolazo-cyclopenten-(I)) lassen sic11 uber die 2-Pyrrdinio-cyclohexanon-( 1)-phenylhydrazon-haloge~ude 3 in befriedigenden Ausbeuten leicht gewinneii orlho-Standige Nitrogruppen in 3 fuhren zu den En-phenylhydrazonen 6. Addition von Piperidin bzw. Methanol an 1-Benzo1azo-cyclohexen-( 1) (4a) bzw. 1 -[p-Nitro-bcnzoldzo]-cycJohcxeii-(I ) (4 b) ergibt JC zwei Stercoisomerc Im Rahmen unserer lintersuehungen uber ZuLkerphenylhydrazonel' und O\azone2-4' bzw. der zuge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…General Remarks: NMR spectra were recorded with Varian Gemini 300 or Mercury 400 spectrometers operating at 300 or 400 MHz (for 1 [2a] and DBDs 3, [19] 4, [20] 5, 6, [21] 7, 18 [22] and 19 were synthesized according to previously reported procedures [23] as (E)/(Z) mixtures in variable relative ratios, depending on the structures. Their characterization data, if not already reported, are described in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…General Remarks: NMR spectra were recorded with Varian Gemini 300 or Mercury 400 spectrometers operating at 300 or 400 MHz (for 1 [2a] and DBDs 3, [19] 4, [20] 5, 6, [21] 7, 18 [22] and 19 were synthesized according to previously reported procedures [23] as (E)/(Z) mixtures in variable relative ratios, depending on the structures. Their characterization data, if not already reported, are described in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…30 "C); v, , , . 1 710 cm-' ((20); m/z 212 [ ( M + 2)+, 4x1, 182 (6), 105 (loo), and 77 (97); (17), 91 (29), and 77 (100).…”
Section: Phn=n-c=omentioning
confidence: 99%
“…We had difficulties in separating analogous catalysts from the final product, and found that the oxidation proceeded satisfactorily in up to 86% yield, in complete absence of catalyst, to give the ketones (15)-( 18) as red oils. In their mass spectra (17) R =o-MeOCsHb (18) R = M e the molecular ion was not normally observable, though significant ( M + 2) peaks were always obtained.…”
mentioning
confidence: 96%
“…Phenylazoalkenes were prepared by published general procedures. [21][22][23] PhenyZazostiZbePie (3) .-Phenylhydraxine (8.64 g, 8 mmol)…”
Section: R I'c=somentioning
confidence: 99%